2021
DOI: 10.1166/sam.2021.3863
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Silver Nanoparticles via Phormidium sp. nov. (Cyanophyceae): Amelioration, Characterization and Assessment of the Antibacterial Potential Against Methicillin Resistant Staphylococcus aureus

Abstract: The use and manufacturing of silver nanoparticles (AgNPs) have recently received considerable attention in many fields. Methicillin resistant Staphylococcus aureus (MRSA) causes infectious diseases in humans. Therefore, the aim of this work was to bio-synthesize AgNPs using the cyanobacteria Phormidium sp. extract and to use this extract with AgNPs to kill MRSA. Extracellular bio-formation of AgNPs by Phormidium sp. was scrutinized at various pH points and temperatures. Then, characterization and assessment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…against multi-drug resistant Staphylococcus aureus (MRSA). Similarly, El- Semary et al (2021) showed the strong antimicrobial activity of silver nanoparticles from a filamentous cyanobacterium. Cyanobacteria grow rapidly in relatively inexpensive growth media.…”
Section: Introductionmentioning
confidence: 95%
“…against multi-drug resistant Staphylococcus aureus (MRSA). Similarly, El- Semary et al (2021) showed the strong antimicrobial activity of silver nanoparticles from a filamentous cyanobacterium. Cyanobacteria grow rapidly in relatively inexpensive growth media.…”
Section: Introductionmentioning
confidence: 95%
“…Several bacteria have been reported for the biosynthesis of AgNPs, including Microvirga rosea [ 22 ], Bacillus sonorensis [ 23 ], Terrabacter humi [ 24 ], etc. There are many recent reports regarding the potent antimicrobial effect of biosynthesized AgNPs against human pathogens [ 25 – 27 ]. Due to the strong antimicrobial action of AgNPs, they are used in the development of footwear, cosmetics, wound dressings and other medical devices [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the antibacterial action of silver nanoparticles, they are incorporated in footwear, cosmetics, wound dressings and plastics [ 11 ]. The antimicrobial effect of silver nanoparticles, biosynthesized by algae against human bacterial pathogens has been previously reported [ 14 , 15 ]. The cyanobacterium under study is unicellular, photosynthetic prokaryotic microorganism.…”
Section: Introductionmentioning
confidence: 99%